Residual Dyslipidemia Leads to Unfavorable Outcomes in Patients with Acute Coronary Syndrome after Percutaneous Coronary Intervention - Bin Que; Chunmei Wang; Hui Ai; Xinyong Zhang; Mei Wang; Shaoping Nie (Hindawi Limited, 2016)
Background. The present study aimed to evaluate the prevalence and prognosis of residual lipid abnormalities in statin-treated acute coronary syndrome (ACS) patients after percutaneous coronary intervention (PCI). Subjects and Methods. A total of 3,047 ACS patients who underwent PCI and received statin therapy were included. Plasma concentrations of LDL-C, HDL-C, and TG were measured. For the follow-up study, major adverse cardiovascular cerebrovascular events (MACCE; including total death, cardiovascular death, myocardial infarction, and revascularization) were documented. Results. A total of 93.14% of all individuals were followed up for 18.1 months (range, 0-29.3 months). Of all 3,047 patients, those with a suboptimal goal were 67.75%, 85.85%, and 33.64% for LDL-C, HDL-C, and TG levels, respectively. Multiple Cox regression analysis revealed there were significant increases in cumulative MACCE of 41% (HR = 1.41, 95% CI [1.09-1.82], p=0.008), and revascularization of 48% (HR = 1.48, 95% CI [1.10-1.99], p=0.01) in low HDL-C patients with ACS after PCI, but not the high TG group at the end of study. Conclusions. Our results showed there is high rate of dyslipidemia in Chinese ACS patients after PCI. Importantly, low HDL-C but not high TG levels are associated with higher MACCE and revascularization rates in ACS patients after PCI.